2012
DOI: 10.1007/s00134-012-2539-7
|View full text |Cite
|
Sign up to set email alerts
|

In-line filtration reduces severe complications and length of stay on pediatric intensive care unit: a prospective, randomized, controlled trial

Abstract: PurposeParticulate contamination due to infusion therapy carries a potential health risk for intensive care patients.MethodsThis single-centre, prospective, randomized controlled trial assessed the effects of filtration of intravenous fluids on the reduction of complications in critically ill children admitted to a pediatric intensive care unit (PICU). A total of 807 subjects were randomly assigned to either a control (n = 406) or filter group (n = 401), with the latter receiving in-line filtration. The primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
105
1
11

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(125 citation statements)
references
References 32 publications
6
105
1
11
Order By: Relevance
“…These particles can come directly from the preparation (glass or rubber fragments) or be linked to the existence of drug incompatibilities in the context of a multi-infusion [20]. The administration of these particles can have serious consequences for the patient, as endothelial lesions and thrombosis [21,22], and the use of inline filters has been shown to reduce the number of general complications and Systemic Inflammatory Response Syndrome (SIRS) [23]. However, a recent meta-analysis did not reveal a significant effect of online filters on overall mortality in pediatrics/neonatology [24].…”
Section: Factorsmentioning
confidence: 99%
“…These particles can come directly from the preparation (glass or rubber fragments) or be linked to the existence of drug incompatibilities in the context of a multi-infusion [20]. The administration of these particles can have serious consequences for the patient, as endothelial lesions and thrombosis [21,22], and the use of inline filters has been shown to reduce the number of general complications and Systemic Inflammatory Response Syndrome (SIRS) [23]. However, a recent meta-analysis did not reveal a significant effect of online filters on overall mortality in pediatrics/neonatology [24].…”
Section: Factorsmentioning
confidence: 99%
“…These authors also showed that particulate contamination could be present downstream from the in-line filter, with particles greater than 10 µm. Nevertheless, the benefits of these filters have been challenged by several authors [3,67,68]. A meta-analysis did not provide specific justification for using in-line IV filters to prevent morbidity and mortality [69] and there may be a problem in clinical practices due to the ineffectiveness of the therapeutic management.…”
Section: Drug Incompatibilities: a Problem In Clinical Practicementioning
confidence: 99%
“…Jack et al [3] designed a prospective study with more than 800 children who were randomly assigned to two groups (with and without in-line filters). This study showed that the occurrence of SIRS was reduced when using 0.22 µm and/or 1.2 µm in-line filters.…”
Section: Systemic Clinical Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the administration of particles through infusion solutions can sometimes result in adverse effects, such as physical occlusion, inflammatory responses, neoplastic responses, and antigenic responses (1). Some reports on pediatric care units have described that in-line filters reduce the overall complication rate and length of stay on pediatric care unit (2); in addition, they also reduce respiratory, renal, and hematological dysfunctions (3) and thrombus formation (4) by preventing particle infusion. In several reviews and guidelines, in-line filters are recommended solely for immunosuppressed patients, newborns, and children (1,5).…”
Section: Introductionmentioning
confidence: 99%